Halfway to good - Murphy, Kirsten (Penguin, 2009)
"Luke is in Year 11 and is a gifted student, but is depressed by his relationship with his dad and the fact that his dad is seriously ill. Anna is a student-teacher who is living with her brother and his son, effectively being a co-parent, while maintaining a long-distance relationship with James (and forgetting about Tom, an ex-flame who reappears on the scene). When Anna's sister Georgie becomes engaged to Luke's brother Oliver, the two narrators lives intersect. This story has witty dialogue; convincing characters; and humour; as well as a more searching theme of finding out what it is about life that makes it worth living and happiness achievable. In Anna's case this involves finding the remarkable in the unremarkable, whether this is through romantic love, or through time spent with family and friends. Or in Luke's case it is a matter of feeling halfway to good (instead of being enveloped in a grey feeling that amounts to depression). In Halfway to Good we have characters in their teens and twenties who have been given distinctive and convincing (often comic) voices that combine cynicism with dry humour. The surface humour deflects the despair they often feel at not finding a sense of ease with themselves or their lives, and it also accompanies the story's more serious themes of coping with illness, death, and grief; workplace bullying; single parenthood; and teen and twenty-something relationships."--Provided by publisher